Radiological Evaluation of Primary Brain Tumors Using Computed Tomography and Magnetic Resonance Imaging - Alsaadi, Khulod; Alkhaldi, Amal; Alhazmi, Fahad (International Journal of Innovative Research in Medical Science, 2017)
Imaging plays a crucial function in the management of patients with brain tumors. The technical improvement of computed tomography (CT) and magnetic resonance (MRI) with the advancement of, brand-new imaging techniques highly enhanced the detection and characterization of brain tumors. This comprehensive review of literature is aimed to discuss the roles of MRI & CT in the diagnosis and evaluation of primary brain tumors, we attempted to discuss the advantage and disadvantage of each modality and which is more effective in this matter. We performed a comprehensive search of literatures among main medical databases; PubMed (MIDLINE), Embase, and science Direct, up to November 2016, to find a relevant article to our study which is discussing the roles of MRI and CT in evaluation of Primary brain tumors. Several terms were used in the search through the databases; (MRI, CT, and Imaging), combined with (Brain cancer, primary brain tumors, glioblastomas). We limited our search to English language studies, and only to Human trails. Computed tomography (CT) might be the very first modality employed in a patient presenting with a brain tumor but for one of the most part MRI is the primary imaging modality in brain tumor patients. The function of CT is mostly relegated to emerging imaging in the detection of hemorrhage, herniation, and hydrocephalus but mass effect from brain tumors and calcification within brain tumors such as oligodendrogliomas or menigiomas can potentially be discovered. The main use of MRI-based medical image analysis for brain tumor studies remains in medical diagnosis, patient tracking and treatment preparation, however it could also be useful in clinical trials.